Mechanisms and bases of resistance in maize to spotted stem borer - Sekhon, S.S.=700 1 Kanta, U.
Sumario (En)
Ilus.; 35 ref.
Keywords: ZEA MAYS; RESISTENCIA A LAS PLAGAS; GERMOPLASMA; ORGANISMOS PARA CONTROL BIOLOGICO; VARIEDADES; FITOTOXICIDAD